The impact of food in the community of São Benedito in the municipality of Nhamundá of the influence of poor food in the capital of Amazonas (Research, Society and Development, 2022)
Introduction: Food is essential for human beings from birth. From food he acquired the nutrients necessary for the functioning of the body, that is, for life. Objective: This study aimed to understand the importance of healthy eating not only because it is a basic need, but also to understand the challenges that the future newly graduated nutritionist has encountered in his career, as well as to describe everything that was collected through of readings. Methodology as a methodology for data collection the bibliographic survey, through the content developed in the theoretical framework on the influence of food in the community of São Benedito in the municipality of Nhamundá in the capital of the Amazon. Results and discussion: riverside people's diet consists of products derived from family activities, such as fishing, livestock, crops of other foods and ultra-processed foods obtained through purchase. Conclusion: it is believed that since the process of building knowledge on this topic is a relevant social problem, it is also expected that the scientific community can awaken to the relevance of the topic by investing more efforts in research and studies, as habits food are important aspects that help to have a good quality of life when performed with good quality nutrients. When it comes to food, one cannot help but think about the consequences of malnutrition.